System development: what, why, when and how CASE tools should support - Sulaiman, Shahida (2007)
The Malaysian Software Engineering Conference (MySEC) is the leading regional conference on software engineering that aims to bring together researchers and practitioners from the academia, industry and government to advance state-of-the-art research and practice in software engineering.